PENGARUH SOLVABILITAS, ARUS KAS OPERASI, ARUS KAS INVESTASI DAN ARUS KAS PENDANAAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR KEUANGAN SUB SEKTOR FINANCING SERVICE YANG TERDAFTAR DI BEI PERIODE 2021-2025 - Rishma Adin Alfina; Hestin Sri Widiawati; Erna Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the phenomenon of declining financial performance among companies in the financial sector, specifically the financing service sub-sector, as indicated by decreasing net income, increasing liabilities, and declining corporate cash balances. These conditions suggest problems in the management of solvency and cash flows, which may affect the companies' ability to generate profits. This study aims to analyze the effect of solvency, operating cash flow, investing cash flow, and financing cash flow on the financial performance of financing service companies listed on the Indonesia Stock Exchange during the 2021–2025 period.This study employed a quantitative approach using secondary data obtained from the companies' annual financial statements published by the Indonesia Stock Exchange. The sample consisted of 11 companies selected through purposive sampling, resulting in a total of 55 observations. The data were analyzed using classical assumption tests, multiple linear regression analysis, the coefficient of determination (R²), partial significance tests (t-test), and simultaneous significance tests (F-test), with the assistance of IBM SPSS software.The results indicate that solvency has a significant effect on financial performance, whereas operating cash flow, investing cash flow, and financing cash flow do not have a significant effect on financial performance. Furthermore, the simultaneous test reveals that solvency, operating cash flow, investing cash flow, and financing cash flow collectively do not have a significant effect on the financial performance of financing service companies listed on the Indonesia Stock Exchange during the 2021–2025 period.